2017
DOI: 10.1038/s41598-017-10581-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of photographs taken by citizens for estimating bumblebee distributions

Abstract: Citizen science is a powerful tool for collecting large volumes of observational data on various species. These data are used to estimate distributions using environmental factors with Species Distribution Models (SDM). However, if citizens are inexperienced in recognizing organisms, they may report different species as the subject species. Here we show nation-wide bumblebee distributions using photographs taken by citizens in our project, and estimated distributions for six bumblebee species using land use, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 48 publications
2
54
0
Order By: Relevance
“…Indeed, in this study a single week of nationwide citizen science sampling generated data with spatial coverage equivalent to more than four decades of expert recording from the UK's current ‘gold standard’ wasp recording scheme. In this, the BWS is not alone; a Japanese citizen science study of bee distribution also performed better than models created with records from the Global Biodiversity Information Faculty (Suzuki‐Ohno et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in this study a single week of nationwide citizen science sampling generated data with spatial coverage equivalent to more than four decades of expert recording from the UK's current ‘gold standard’ wasp recording scheme. In this, the BWS is not alone; a Japanese citizen science study of bee distribution also performed better than models created with records from the Global Biodiversity Information Faculty (Suzuki‐Ohno et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in this study a single week of nationwide citizen science sampling generated data with spatial coverage equivalent to more than four decades of expert recording from the UK's current 'gold standard' wasp recording scheme. In this, the BWS is not alone; a Japanese citizen science study of bee distribution also performed better than models created with records from the Global Biodiversity Information Faculty (Suzuki-Ohno et al, 2017). Critical to this success, BWS data were collected using a standardised method that took advantage of the ubiquity and enthusiasm of the public even for uncharismatic species like wasps, resulting in large sample sizes and high geographical coverage. Moreover, identification to species level, always a potential weak link in citizen science projects, was undertaken by experts.…”
Section: Discussionmentioning
confidence: 99%
“…The question arises as to whether B. ardens ardens is also a pollinator of D. kaki in other regions. This bumblebee is distributed almost throughout Japan, except Hokkaido, which is inhabited by another subspecies, Bombus ardens sakagamii Tkalců (Hymenoptera: Apidae), and the Okinawa Islands (Tadauchi and Murao 2014;Suzuki-Ohno et al 2017). Some studies have reported that B. ardens ardens relies on tree flowers rather than herbaceous ones (Osada et al 2003;Ushimaru et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For these studies, we used threatened plant distribution data collected by the Japanese Ministry of Environment to establish a national red list (https://ikilog.biodic.go.jp/Rdb/booklist). In the 2010s, the number of macroecological studies (based on integrated reusable data) covering the entire Japanese archipelago increased dramatically (Amano et al, ; Kadoya & Washitani, ; Naoe et al, ; Saito, Kurashima, & Ito, ; Suzuki‐Ohno, Yokoyama, Nakashizuka, & Kawata, ; Yoshioka, Fukasawa, Mishima, Sasaki, & Kadoya, ).…”
Section: Ecological Research Based On Existing Datamentioning
confidence: 99%
“…Recently, citizen science approaches (e.g., field observations by members of the public) have generated increasing interest in ecology and biodiversity sciences (Kobori et al, 2016;Osawa, Yamanaka, et al, 2017). One important research benefit provided by citizen science is the crowdsourcing of large datasets (Osawa, 2015;Osawa, Yamanaka, et al, 2017;Suzuki-Ohno et al, 2017). Suzuki-Ohno et al (2017) estimated the potential distribution ranges of six bumblebees based on photographs taken by citizens throughout Japan.…”
Section: Citizen Science Datamentioning
confidence: 99%